High EZH2 expression is correlated to metastatic disease in pediatric soft tissue sarcomas. Issue 1 (December 2016) - Ramaglia, Maria; D'Angelo, Velia; Iannotta, Adriana; Pinto, Daniela; Pota, Elvira; Affinita, Maria; Donofrio, Vittoria; Errico, Maria; Lombardi, Angela; Indolfi, Cristiana; Casale, Fiorina; Caraglia, Michele
Abstract Background Enhancer of ZesteDrosophila Homologue 2 (EZH2) is a key regulator of transcription as a member of polycomb repressive complex 2 (PRC2) which exerts repression of downstream genes and is correlated to invasiveness and progression of different tumours. Therefore, we evaluated the expression of PRC2 proteins in pediatric soft tissue sarcoma (rhabdomyosarcoma, RMS and extraosseous Ewing sarcoma, EES) correlating them to the clinical outcome of the patients. Methods We analyzed PRC2 protein expression by quantitative real time PCR, western blotting and immunohistochemistry in 17 soft tissue sarcomas (11 RMS and 6 EES) enrolled at Paediatric Oncology Units of the Second University of Naples. Expression analysis was performed for EZH2, SUZ12 and EED. Results Enhancer of ZesteDrosophila Homologue 2 was expressed with a different degree in 60 % of samples. Interestingly, the magnitude of EZH2 up regulation was significantly higher in patients presenting lymph node and/or distant metastases at the diagnosis. Moreover, patients overexpressing EZH2 had a lower probability of survival compared to patients negative or with low EZH2 expression. Conclusions Our study suggests that high EZH2 expression is associated to increased aggressiveness of the disease. Therefore, drugs that control its activity could be potentially used in the epigenetic target treatment of tumors with these alterations.